Damage induced by monotonic and cyclic spherical indentation in polycrystalline diamond (PCD). (March 2015) - Marro, F.G.; Mestra, A.; Jiménez-Piqué, E.; Ozbayraktar, S.; Llanes, L.
Abstract: The spherical indentation technique has been successfully implemented for inducing controlled damage, under both monotonic and cyclic loading conditions, in three microstructurally different polycrystalline diamond (PCD) grades. Damage evolution under increasing applied load and/or number of cycles has been assessed, and the attained results point out the important role of microstructure on nature, aspect and evolution of damage in these materials. At the microscopic level, transgranular fracture of diamond particles and crack propagation through the binder matrix are found to be the predominant crack paths for damage induced under contact loads in all the cases. Highlights: Spherical indentation as a valid technique to induce controlled damage on PCD Spherical indentation as a valid technique to evaluate damage evolution on PCD Cracking scenario depends on PCD's microstructure and loading conditions. PCD's contact damage mechanisms are correlated to microstructure and loading condition.